2021 Focused update of the 2017 consensus guidelines of the Asia Pacific Heart Rhythm Society (APHRS) on stroke prevention in atrial fibrillation - Chao, Tze‐Fan; Joung, Boyoung; Takahashi, Yoshihide; Lim, Toon Wei; Choi, Eue‐Keun; Chan, Yi‐Hsin; Guo, Yutao; Sriratanasathavorn, Charn; Oh, Seil; Okumura, Ken; Lip, Gregory Y. H. (Journal of arrhythmia, 2021)
The consensus of the Asia Pacific Heart Rhythm Society (APHRS) on stroke prevention in atrial fibrillation (AF) has been published in 2017 which provided useful clinical guidance for cardiologists, neurologists, geriatricians, and general practitioners in Asia‐Pacific region. In these years, many important new data regarding stroke prevention in AF were reported. The Practice Guidelines subcommittee members comprehensively reviewed updated information on stroke prevention in AF, and summarized them in this 2021 focused update of the 2017 consensus guidelines of the APHRS on stroke prevention in AF. We highlighted and focused on several issues, including the importance of AF Better Care (ABC) pathway, the advantages of non–vitamin K antagonist oral anticoagulants (NOACs) for Asians, the considerations of use of NOACs for Asian patients with AF with single 1 stroke risk factor beyond gender, the role of lifestyle factors on stroke risk, the use of oral anticoagulants during the “coronavirus disease 2019” (COVID‐19) pandemic, etc. We fully realize that there are gaps, unaddressed questions, and many areas of uncertainty and debate in the current knowledge of AF, and the physician's decision remains the most important factor in the management of AF. We aim to publish the APHRS consensus simultaneously with the APHRS annual scientific meeting.